Rostral mandibulectomy for the management of trismus in a cat. Issue 1 (February 2022) - Parsons, Kevin; Langley-Hobbs, Sorrel; Warren-Smith, Christopher; Southerden, Peter; Granger, Nicolas; Meakin, Lee
Case summary: A 5-year-old domestic shorthair cat was evaluated for weight loss and poor coat condition due to an inability to open its mouth (trismus) following head trauma 2 months previously. Contrast CT, electromyography and temporal muscle biopsy identified findings consistent with muscle atrophy, denervation and degeneration. Conservative treatment failed to improve the trismus so a rostral mandibulectomy was performed. Following surgery, the patient resumed normal grooming behaviour and was able to eat soft food unaided. The cat re-presented 5 months postoperatively at which time its body condition had improved; however, episodes of sneezing had been noted. An oronasal fistula was diagnosed and treated successfully with a silicon nasal septum button. Follow-up at 30 months reported an excellent outcome. Relevance and novel information: Management of trismus with rostral mandibulectomy may be associated with a good return to function, including prehension and ingestion of food, and restoration of normal grooming activity. Rostral mandibulectomy could be considered for animals with trismus for other aetiologies such as masticatory myositis where other management options are not available.